Evaluation of VITEK 2 Rapid Identification and Susceptibility Testing System against Gram-Negative Clinical Isolates - Thomas K.W. Ling; Po Chu Tam; Z. K. Liu; Augustine F. Cheng (2001)
ABSTRACT A total of 281 strains of miscellaneous members of the family Enterobacteriaceae , Pseudomonas aeruginosa , and other gram-negative bacteria were evaluated by use of identification tests with the VITEK 2 system (bioMérieux) and an API identification system (bioMérieux). A total of 237 (95%) strains were correctly identified to the species level. Only six (2.1%) strains were misidentified, and eight (2.8%) strains were not identified. Among 14 strains with discrepant identifications, 8 (57.1%) strains were nonfermenters. The susceptibilities of 228 strains to 11 antibiotics including amikacin, netilmicin, tobramycin, gentamicin, ciprofloxacin, imipenem, meropenem, ceftazidime, cefepime, piperacillin, and piperacillin in combination with tazobactam were tested with the VITEK 2 AST-No. 12 card and by the broth microdilution (MB) method, according to NCCLS guidelines, as a reference. For the 2,508 organism-antibiotic combinations, the rates at which duplicate MICs correlated within ±1 dilution ranged from 84.2 to 95.6%. Only 13 (0.5%) and 10 (0.4%) of the susceptibility tests gave major errors (resistant with the VITEK 2 system but sensitive by the MB method) and very major errors (sensitive with the VITEK 2 system but resistant by the MB method), respectively. Both VITEK 2 ID-GNB (an identification system) and VITEK 2 AST-No. 12 (a susceptibility testing system) card systems gave rapid, reliable, and highly reproducible results.